Geographical variation in cardiovascular incidence: results from the British Women's Heart and Health Study - Ebrahim Shah; Lawlor Debbie A; Carson Claire; Kim Lois G (BMC, 2010)
Abstract Background Prevalence of cardiovascular disease (CVD) in women shows regional variations not explained by common risk factors. Analysis of CVD incidence will provide insight into whether there is further divergence between regions with increasing age. Methods Seven-year follow-up data on 2685 women aged 59-80 (mean 69) at baseline from 23 towns in the UK were available from the British Women's Heart and Health Study. Time to fatal or non-fatal CVD was analyzed using Cox regression with adjustment for risk factors, using multiple imputation for missing values. Results Compared to South England, CVD incidence is similar in North England (HR 1.05 (95% CI 0.84, 1.31)) and Scotland (0.93 (0.68, 1.27)), but lower in Midlands/Wales (0.85 (0.64, 1.12)). Event severity influenced regional variation, with South England showing lower fatal incident CVD than other regions, but higher non-fatal incident CVD. Kaplan-Meier plots suggested that regional divergence in CVD occurred before baseline (before mean baseline age of 69). Conclusions In women, regional differences in CVD early in adult life do not further diverge in later life. This may be due to regional differences in early detection, survivorship of women entering the study, or event severity. Targeting health care resources for CVD by geographic variation may not be appropriate for older age-groups.